A review on numerical modelling of flashing flow with application to nuclear safety analysis. (5th January 2021) - Liao, Yixiang; Lucas, Dirk
Highlights: A review on numerical modelling of nuclear flashing flows is provided. Consideration of interphase slip with a two-fluid model is often necessary. Thermal, velocity and pressure effects all affect the vaporization rate. Poly-disperse models considering different interfacial topologies are promising. Abstract: The flashing flow is a relevant multiphase phenomenon in many technical applications including nuclear safety analysis, which has been the subject of intense research for several decades. Numerical studies have evolved from one-dimensional to multi-dimensional. A variety of methods has been proposed, while a broad consensus does not exist yet. The present work aims to present an overview of available models and assess their limitations and perspectives by conducting an extensive literature survey. The final focus was put on recent progresses of computational fluid dynamics simulations. Some consensus on modelling interfacial slip, phase change mechanism and bubble size is identified. Since flashing scenarios often accompanying with high void fraction and broad bubble size range, a poly-disperse two-fluid model is recommended. Thermal phase change model is superior to pressure phase change, relaxation and equilibrium models for practical flashing problems, however incorporation of pressure effects is desirable. Major challenges comprise improving closure models for interphase transfer, bubble dynamics processes, interfacial area as well two-phase turbulence. For this purpose, high-resolution high quality experimental data are important, which are lacking in many cases. Considering that heterogeneous gas structures often exist in flashing flows, multi-field approaches able to handle different shapes of gas-liquid interface and including the shape effect in closure models are recommended for further study.